1994
DOI: 10.1111/j.1432-1033.1994.tb18630.x
|View full text |Cite
|
Sign up to set email alerts
|

Pore formation in artificial membranes by the secreted hemolysins of Proteus vulgaris and Morganella morganii

Abstract: Lipid-bilayer experiments were performed with the related hemolysins from Proteus vulgaris and Morganella morganii (HlyA). The addition of the toxins to the aqueous phase bathing lipidbilayer membranes composed of different lipids resulted in the formation of transient ion-permeable channels. Membranes formed of pure lipids were rather inactive targets for the hemolysins as compared with lipid mixtures such as asolectin. The channels had several different substates. The major open state had single-channel cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 48 publications
(36 reference statements)
9
45
0
Order By: Relevance
“…A quantitative description of the effect of point charges on single-channel conductance may be given by the treatment proposed by Nelson and McQuarrie (25). It describes the effect of point charges on the conductance of a channel, which is dependent on ion concentration, on the channel diameter, and on the number of negative charges (5). A comparison of the crystal structure of the Rhodobacter capsulatus porin with the diameter derived from this theoretical treatment yields good agreement (30).…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…A quantitative description of the effect of point charges on single-channel conductance may be given by the treatment proposed by Nelson and McQuarrie (25). It describes the effect of point charges on the conductance of a channel, which is dependent on ion concentration, on the channel diameter, and on the number of negative charges (5). A comparison of the crystal structure of the Rhodobacter capsulatus porin with the diameter derived from this theoretical treatment yields good agreement (30).…”
Section: Methodsmentioning
confidence: 57%
“…Accordingly, they influence both single-channel conductance and zero-current membrane potential, and the single-channel conductance is much larger than expected from the dimensions of the channel. A quantitative description of the effect of the point charges on the single-channel conductance may be given with the considerations of Nelson and McQuarrie (25), as previously described (5). A best fit of the data of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result seems to represent a contradiction to the obvious receptor-mediated permeabilization of cells. However, it has to be kept in mind that other toxins, such as C2 toxin (20) or the repeat in toxin toxins (27)(28)(29), form channels in lipid bilayer membranes without the need for receptors, whereas they all need a receptor for biological activity. An important role of the toxin receptor in events finally resulting in channel formation is supported by the concentration effect studies at high concentration of toxin, which show that limitation of channel formation is most likely due to reaching the binding capacity of cells.…”
Section: Rbmentioning
confidence: 99%
“…This means that they were mostly in the open configuration and did not close under our experimental conditions. This result indicated that the channel was formed by a defined structure, which does not show an associationdissociation equilibrium, such as the oligomers that form the hemolysin channels of Proteus vulgaris and Morganella morganii (25). A histogram of the channels formed by the activated C. perfringens epsilon toxin under the conditions of Fig.…”
Section: Activation Increases the Channel-forming Activity Of C Perfmentioning
confidence: 99%